Values present in the landscape of the city of Pachuca, Hidalgo, Mexico (2021)
This research is part of the thesis work done to obtain a PhD in Design, Planning and Conservation of Landscapes and Gardens, at the Autonomous Metropolitan University, Azcapotzalco Unit, whose title is: Revaluation of the Cultural Heritage of the City of Pachuca, Hidalgo, Mexico. However, before being able to approach the concept of revaluation, it is necessary to define what a value is and how it is identified within the components of the city landscape. So, it is intended to describe the values of the landscape present in the study area, which make this metropolis an iconic site for its history, mineral wealth, topography, and culture. The method of the Metropolitan Situation Analysis (MESA), conceived by the program “Training for Education, Learning and Leadership Towards a New Metropolitan discipline Tell me”, belonging to the international network of research on cities and metropolises, has been taken as a reference. coordinated by the Faculty of Architecture of the Polytechnic of Milan, Italy, through the Erasmus Plus Program of the European Union, 2014-2020 and the document of the Catalog of Landscapes of the Barcelona Metropolitan Region (2017) as well as an exhaustive compilation of documentary, bibliographic, cartographic and photographic information, as well as tours of the city, all with a view to disseminating information that allows the revaluation of the city’s Cultural Heritage through the landscape values present in it.